Examining the Effects of Agomelatine on Uterine Activity of Rats in Which Agomelatine Is Used during, before and in Various Stages of Pregnancy - Kacar, Emine; Tan, Fatih (Karger, 2018)
[Abstract Not Available]
3rd International Congress of the Turkish-Neuroendocrinology-Society -- JUN 29-JUL 01, 2018 -- Malatya, TURKEY